The Effect of Salary Satisfaction, Work Satisfaction and Organizational Commitment To Work Intention - Meithiana Indrasari; Bambang Raditya Purnomo; Eddy Yunus; Eny Haryati; Abdul Razzak Hashmi (Jurnal Didaskalia, 2018)
High rate of turnover leads to adverse effect to an organization. Such problem is likely generating instability and uncertainty towards employment condition and human resources cost rise in forms of training invested to them, recruitment and newly built training programs. High turnover, in addition, also results in organizational ineffectiveness because it loses experienced employees as well as spends much times in training new, inexperienced employees. This study aims to analyze the effect of salary satisfaction, work satisfaction and organizational commitment on withdrawal intention and to analyze the most affective variable on withdrawal intention. There are 115 respondents for the samples and data analysis during the research is held by using SEM and AMOS 5 program. According to the analysis, it is concluded as the followings: work satisfaction has a positive effect on organizational commitment (CR = 6.052); salary satisfaction has a negative effect on turnover (CR = -4.306); job satisfaction has a negative effect on turnover (CR = -4.846); and organizational commitment has a negative effect on turnover (CR = -2.822).